En Bloc Resection of Primary Large Esophageal Mucosa-Associated Lymphoid Tissue Lymphoma by Endoscopic Submucosal Dissection: A Case Report - Xia, Yujia; Wang, Yu; Han, Jian; Liu, Mei (Frontiers in Medicine, 2021)
Treatment of mucosa-associated lymphoid tissue (MALT) lymphoma has recently received considerable attention. Here, we report a case of large esophageal MALT lymphoma that was successfully en bloc resected using endoscopic submucosal dissection (ESD). A 77-year-old woman was admitted to our hospital with progressive dysphagia for more than 2 months. Upper gastrointestinal endoscopy revealed a large rounded submucosal mass covered by normal mucosa, located at the lower esophagus. Endoscopic ultrasonography (EUS) showed a well-demarcated hypoechoic mass chiefly located in the esophageal wall, but the layers of esophageal wall are not clear. ESD was performed for diagnostic and treatment purpose. No complication occurred during or after ESD. The resected specimen was measured 4.3× 2.8× 1.5 cm. The histologic findings were diagnostic of esophageal MALT lymphoma. Infiltration of neoplastic cells in the lateral margins of the resected specimen was not observed. However, vertical margins showed an R1 situation and mild damage to the muscularis propria. After 3 months, her dysphagia disappeared. Then additional radiation therapy was administered. After 5 months, the patient was still under surveillance and free of recurrent disease. Resection with ESD of such a large mass of MALT in the esophageal region has rarely been reported before in the literature.